Changing attitudes: lessons for countering the trafficking of cultural objects - Runhovde, Siv Rebekka (Global crime, 2022)
The illicit transnational trades in cultural goods and wildlife, while distinct, share many characteristics. This article identifies and compares the intricacies of controlling trafficking in cultural objects and wildlife from a customs perspective. Findings indicate that in Norwegian customs, the countering of wildlife trafficking benefits from at least two conditions: 1) officers have become more aware of the characteristics and harmful consequences of the trade, and 2) efficient interactions with other stakeholders ensure tangible outcomes in the form of seizures and punishment of offenders. While challenges remain, these factors serve to motivate officers and, in the last decade, have strengthened the control of wildlife trafficking. The countering of illicit trade in cultural objects, however, does not benefit from such circumstances. Findings suggest that the officers’ awareness of, and attitude towards, trafficking of such materials are key factors to consider for evolving the response.